2023
DOI: 10.3390/vaccines11030642
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of COVID-19 Vaccines: Protective Shields or Threatening Risks? A Descriptive Exploratory Study among the Italian Population

Abstract: Although several quantitative studies have explored vaccine hesitancy, qualitative research on the factors underlying attitudes toward vaccination is still lacking. To fill this gap, this study aimed to investigate the general perceptions of COVID-19 vaccines among the Italian population with a qualitative approach. The sample included 700 Italian participants who completed an online survey. Open questions underwent a descriptive analysis for unveiling meaning categories, while differences in the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Halbrook et al, 2022;Wang et al, 2020) or hesitation (Baniak et al, 2021;Biswas et al, 2021;Halbrook et al, 2022;Shekhar et al, 2021). A study conducted by Boragno et al (2023) revealed that healthcare providers more frequently used words with 'trust' and 'safety' themes about the vaccine compared to non-healthcare providers. The current study found that nurses' scores on the positive attitude towards the COVID-19 vaccine subscale were higher than their negative attitude scores.…”
Section: Discussionmentioning
confidence: 99%
“…Halbrook et al, 2022;Wang et al, 2020) or hesitation (Baniak et al, 2021;Biswas et al, 2021;Halbrook et al, 2022;Shekhar et al, 2021). A study conducted by Boragno et al (2023) revealed that healthcare providers more frequently used words with 'trust' and 'safety' themes about the vaccine compared to non-healthcare providers. The current study found that nurses' scores on the positive attitude towards the COVID-19 vaccine subscale were higher than their negative attitude scores.…”
Section: Discussionmentioning
confidence: 99%